Small Business Performance Drivers; Market Orientation and Business Capabilities Perspectives - Helman Fachri; Joko Rizkie Widokarti; Harry A.P. Sitaniapessy (Univiversitas Dr. Djar Wattiheluw, 2024)
This research, focusing on Sambas Regency, investigates how Market Orientation and Business Capabilities influence small business performance in the West Kalimantan - Sarawak border area. Through a survey of 50 small business owners operating via the Aruk Border Post, the study found that both Market Orientation and Business Capabilities significantly impact business performance. Market orientation, requiring significant resources and focus, business capabilities, and support for performance improvement are crucial factors. The study recommends prioritizing innovation and adaptation to market needs, enhancing collaboration and resource optimization, and utilizing cross- border cooperation and digital technology for broader market access to develop business strategies sustainably.